2022
DOI: 10.3390/polym14142785
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Behavior of Carbon Fibers in Ceramizable Phenolic Resin Matrix Composites at Elevated Temperatures

Abstract: Carbon fiber fabric-reinforced phenolic resin composites are widely used as thermal protection materials for thermal protection systems in hypersonic vehicles and capsules. In this work, carbon fiber fabric-reinforced boron phenolic resin composites modified with MoSi2 and B4C were prepared via a compression molding technique. The high-temperature performance of the composites as well as the oxidation behavior of the carbon fibers was studied. The results indicate that the incorporation of B4C improves the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
(63 reference statements)
1
1
0
Order By: Relevance
“…Compression molding involves the uniform mixing of BPF with reinforced fibers, special fillers, or rubber to prepare premix [102,[106][107][108][109][110][111]. Alternatively, fiber cloth can be immersed in BPF solution to prepare prepreg [8,33,87,99,100,103,105,112,113]. The prepreg is then dried, placed in a mold, and sealed under heat and pressure to crosslink and solidify the resin.…”
Section: Compression Moldingmentioning
confidence: 99%
“…Compression molding involves the uniform mixing of BPF with reinforced fibers, special fillers, or rubber to prepare premix [102,[106][107][108][109][110][111]. Alternatively, fiber cloth can be immersed in BPF solution to prepare prepreg [8,33,87,99,100,103,105,112,113]. The prepreg is then dried, placed in a mold, and sealed under heat and pressure to crosslink and solidify the resin.…”
Section: Compression Moldingmentioning
confidence: 99%
“…The peak at around 1600 cm −1 was called the G band, corresponding to an ideal graphite lattice, whereas the peak at around 1350 cm −1 was called the D band, corresponding to a graphite lattice with defects. Therefore, the intensity ratio of the G band to the D band (I G /I D ) can be used to estimate defects in carbon materials [8,20]. A larger I G /I D value indicates fewer defects and a higher degree of graphitization.…”
Section: Oxyacetylene Ablation Behaviormentioning
confidence: 99%
“…Similarly, CF/Ph is also prone to oxidation failure. The oxidation resistance and ablation resistance of CF/Ph could be significantly improved via matrix modification and fiber-coating strategies [5,8,20]. For example, Chang et al reported an Al 2 O 3f -CF/Ph modified with HfB 2 and SiB 6 that achieves a linear ablation rate (LAR) of 0.06 mm/s [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural performance of polymers and fiber-reinforced polymer composites can be enhanced through the addition of filler materials such as carbon nanotube (CNT), graphene, graphene oxide (GO), nanoclay, non-metallic oxides and carbides, and metallic oxides, carbides, borides, silicates, and silicides. The modification of matrices of CFRP composites with nano- and microfillers has been reported to lead to considerable improvement in their ablation resistance [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ], interlaminar shear strength (ILSS) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ], interlaminar fracture toughness (ILFT) [ 22 , 28 , 29 , 30 ], wear and tribological properties [ 31 , 32 , 33 ], as well as flexural properties (strength and elastic modulus) [ 34 , 35 ]. Xu et al [ 13 ] studied the ablation resistance and mechanism of CF-fabric-reinforced phenolic resin composite modified with particles of tantalum disilicide (TaSi 2 ) and reported significant improvement in the anti-ablation property of TaSi 2 -modified composite in comparison with the unmodified composite.…”
Section: Introductionmentioning
confidence: 99%